Pengabdian Anak Nagari untuk Luak 50 dalam Upaya Pencegahan Penyebaran Covid-19 Melalui Kerja Nyata dan Maya - Nilda Tri Putri; Ahmad Ahmad; Lona Delviari; Melani Putri; Viola Kiswara; Rhima Suryani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
The Covid-19 pandemic which has become a national disaster in Indonesia has changed various aspects of life. Payakumbuh City and 50 Kota Regency are examples of areas affected by Covid-19. Seeing this, students of the Faculty of Engineering, Andalas University have served the community in order to reduce Covid-19. This activity was carried out by providing education related to health protocols to the community, making hand washing equipment equipped with sensors and foot pedals, making tools in the form of sterilization booths that can be used by people in Payakumbuh City and 50 Kota Regency. In addition, this activity was also carried out in the form of educational videos in cyberspace related to how to deal with the Covid-19 pandemic in order to stay healthy and be able to break the chain of the spread of Covid-19. The benefits of the activities carried out for the surrounding community are that the community is more sensitive and cares more about health protocols such as wearing masks, washing hands. As well as reducing the spread of the spread of Covid-19 in public service offices such as banks in Payakumbuh City. Then the community also received education regarding the use of yards in planting living kitchens for the survival of people affected by the Covid-19 pandemic.